Polyurethane foam and method for producing the same
Patent Information
- Application Number
- JP2023128167
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2043-08-04
AI Technical Summary
【0009】 本発明によれば、高難燃性を有しながら、低硬度で、復元性に優れたポリウレタンフォーム及びその製造方法を提供することができる。
Smart Images

Figure 2025023749000004 
Figure 2025023749000001 
Figure 2025023749000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyurethane foam and a method for producing the same. [Background technology]
[0002] Polyurethane foams are used in a wide range of applications, such as sponges, cushions used in speakers and headphones, bed cushions and mats, shoe insoles, and insulation materials.
[0003] Heat resistance and flame retardancy are among the properties required for plastic materials. However, among plastic materials, polyurethane foam has low density and good breathability, making it flammable, and so far attempts have been made to improve its flame retardancy.
[0004] As a method for making polyurethane foam flame retardant, a method in which a flame retardant is added in advance to a raw material composition of the polyurethane foam is known. For example, Patent Document 1 discloses a flame-retardant polyurethane foam obtained by foaming a polyurethane foam formulation containing a flame retardant containing a phosphorus-based flame retardant, a melamine flame retardant, and expandable graphite. Furthermore, Patent Document 2 discloses a foam-molded product having excellent flame retardancy obtained by foam molding a polyurethane raw material composition containing a composite flame retardant consisting of a binary system of a first flame retardant made of carbon and a second flame retardant made of red phosphorus and a condensed phosphate ester. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-252111 A [Patent Document 2] JP 2012-97169 A Summary of the Invention [Problem to be solved by the invention]
[0006] Meanwhile, polyurethane foams are required to have high flame retardancy while also exhibiting the inherent properties of polyurethane foams, such as low hardness and excellent recovery properties. However, the polyurethane foams disclosed in Patent Documents 1 and 2, including those disclosed in Patent Documents 1 and 2, are still insufficient in terms of both excellent flame retardancy and mechanical properties, and further improvements are currently required.
[0007] Therefore, an object of the present invention is to provide a polyurethane foam which has high flame retardancy, low hardness and excellent recovery property, and a method for producing the same. [Means for solving the problem]
[0008] Means for solving the above problems include the following aspects. <1> Polyether polyol A, Isocyanate B of the diphenylmethane diisocyanate series, Water C and Catalyst D; a flame retardant E containing expanded graphite, a phosphorus-based flame retardant, and aluminum hydroxide; A polyurethane foam comprising a foam of a composition comprising: <2> The content of the expanded graphite is 40 to 80 parts by mass relative to 100 parts by mass of the polyether polyol A, The content of the phosphorus-based flame retardant is 15 to 40 parts by mass relative to 100 parts by mass of the polyether polyol A, The content of the aluminum hydroxide is 10 to 30 parts by mass relative to 100 parts by mass of the polyether polyol A. <1> 2. The polyurethane foam according to claim 1 . <3> The thickness is less than 6mm and the apparent density is 270-370kg / m 3 That is, <1> or <2> 2. The polyurethane foam according to claim 1 . <4> 25% compression hardness is 0.1MPa or less. <1> ~ <3> 13. The polyurethane foam according to claim 12. <5> 50% compression residual strain is 5% or less. <1> ~ <4> 13. The polyurethane foam according to claim 12. <6> A step of extruding a composition including polyether polyol A, a diphenylmethane diisocyanate-based isocyanate B, water C, a catalyst D, and a flame retardant E including expandable graphite, a phosphorus-based flame retardant, and aluminum hydroxide from a die to obtain a coating film; Heating the coating; The method for producing a polyurethane foam comprising the steps of: <7> The content of the expanded graphite is 0.15 to 0.25 in terms of a mass ratio relative to the composition, The content of the phosphorus-based flame retardant is 0.05 to 0.13 in terms of mass ratio relative to the composition, The content of the aluminum hydroxide is 0.03 to 0.10 in terms of mass ratio relative to the composition. <6> A method for producing a polyurethane foam according to claim 1. Effect of the Invention
[0009] According to the present invention, it is possible to provide a polyurethane foam having high flame retardancy, low hardness and excellent recovery property, and a method for producing the same. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram showing an example of an apparatus configuration for carrying out a method for producing a polyurethane foam according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described as an example. In the numerical ranges described in the present embodiment, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range described in the present embodiment. In addition, in the numerical ranges described in the present embodiment, the upper or lower limit of the numerical range may be replaced with a value shown in the examples. In this embodiment, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. When the embodiment is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. Furthermore, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this. In this embodiment, each component may contain multiple types of corresponding substances. When referring to the amount of each component in the composition in this embodiment, if multiple types of substances corresponding to each component are present in the composition, the amount refers to the total amount of the multiple types of substances present in the composition, unless otherwise specified.
[0012] (Polyurethane foam) The polyurethane foam according to this embodiment is Polyether polyol A, Isocyanate B of the diphenylmethane diisocyanate series, Water C and Catalyst D; a flame retardant E containing expanded graphite, a phosphorus-based flame retardant, and aluminum hydroxide; The foam comprises a composition comprising: The composition for forming the foam (hereinafter also referred to as "urethane raw material liquid") may contain other components in addition to the above components.
[0013] The polyurethane foam according to the present embodiment has the above-mentioned constitution, and while having high flame retardancy, it also has low hardness and excellent recovery property. The reason for this is presumed to be as follows.
[0014] In this embodiment, a combination of expanded graphite, a phosphorus-based flame retardant, and aluminum hydroxide is used as the flame retardant E. In this combination, the expanded graphite is heated such that the acid intercalated between the graphite layers vaporizes, widening the gap between the layers to form a char layer (thermal carbonization layer) whose volume expands by 200 times or more, and acts as a flame retardant. Phosphorus-based flame retardants act to retard flames by promoting carbonization during combustion, forming a char layer (thermal carbonization layer), and by trapping radicals in the gas phase. Aluminum hydroxide acts to provide flame retardancy through a cooling effect due to an endothermic dehydration reaction during combustion, a dilution effect of the combustion gas in the gas phase due to the water produced, and a heat insulating effect of the inorganic oxide layer produced. On the other hand, aluminum hydroxide is believed to have the effect of uniformly dispersing the expanded graphite in the urethane raw material liquid during the production of polyurethane foam. Therefore, even after the process described below (e.g., via a die coater), the resulting polyurethane sheet is uniformly imparted with flame retardancy throughout the entire sheet. As a result, it is believed that excellent high flame retardancy is exhibited. In addition, the inclusion of solid components of expanded graphite and aluminum hydroxide in urethane foam increases the hardness of the urethane foam. On the other hand, liquid phosphorus-based flame retardants also act as plasticizers, and when included in urethane foam, they tend to reduce the hardness. Therefore, it is believed that the combined use of three types of flame retardants can suppress the increase in hardness. In addition, the combined use of three types of flame retardants can obtain high flame retardancy with a smaller total amount than the use of only one or two types of flame retardants, so that the reduction in the total content of the flame retardants does not impair the performance of the urethane foam and suppresses the decrease in recovery.
[0015] From the above, it is presumed that the polyurethane foam according to this embodiment has high flame retardancy, low hardness, and excellent recovery properties due to the above-mentioned configuration. In particular, the polyurethane foam according to this embodiment has high flame retardancy even when it is thin (for example, as thin as 2 mm).
[0016] Each component of the urethane raw material liquid will now be described.
[0017] (Polyether polyol A) The polyether polyol A includes alkylene oxide-added polyether polyols and the like. Among these, as the polyether polyol A, an alkylene oxide-added polyether polyol is preferable.
[0018] Alkylene oxide-added polyether polyol is a compound obtained by addition polymerization of alkylene oxide (ethylene oxide, propylene oxide, copolymer of ethylene oxide and propylene oxide, tetramethylene oxide (tetrahydrofuran, THF), etc.) to low molecular weight alcohol (ethylene glycol, glycerin, trimethylolpropane, etc.). As the alkylene oxide-added polyether polyol, polypropylene glycol (PPG), polyethylene glycol (PEG), a copolymer of PPG and PEG, polytetramethylene ether glycol (PTMG), and the like are preferable.
[0019] In particular, the polyether polyol A is preferably an alkylene oxide-added polyol in which propylene oxide and ethylene oxide are added to a low molecular weight alcohol, and the molar ratio of ethylene oxide is 5 to 30% (preferably 10 to 30%). The molar ratio of ethylene oxide may be adjusted to within the range of 5 to 30% by mixing two or more kinds of polyether polyol A.
[0020] The number of functional groups f of the polyether polyol A is preferably 2 to 3 from the viewpoints of low 25% compression hardness and low 50% compression set.
[0021] The number average molecular weight Mn of the polyether polyol A is preferably from 1,000 to 10,000, and more preferably from 3,000 to 8,000, from the viewpoints of low 25% compression hardness and low 50% compression set. Here, the number average molecular weight is the molecular weight calculated from the measured value of the hydroxyl value and the number of functional groups according to JIS K 0070-1992. The number average molecular weights of other components are also measured in the same manner.
[0022] (Diphenylmethane diisocyanate-based isocyanate B) Diphenylmethane diisocyanate-based isocyanate B is an isocyanate having a diphenylmethane diisocyanate skeleton.
[0023] Examples of diphenylmethane diisocyanate-based isocyanate B include 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-MDI, and 2,2'-MDI. The diphenylmethane diisocyanate-based isocyanate B may be monomeric MDI (pure MDI) or polymeric MDI (crude MDI). It may also be modified MDI such as carbodiimide-modified MDI, polyol-modified MDI, or prepolymer-modified MDI. In particular, it is preferable to use two or more types of diphenylmethane diisocyanate-based isocyanate B from the viewpoint of low 25% compression hardness and low 50% compression set. When used alone, the polyurethane-forming reaction may be fast or extremely slow, making it difficult to control the reaction. In addition, the resulting polyurethane foam is likely to have low 25% compression hardness and low 50% compression set.
[0024] The isocyanate index (NCO index) of the diphenylmethane diisocyanate-based isocyanate B is preferably 80-120.
[0025] The isocyanate index is the value obtained by dividing the number of moles of isocyanate groups in an isocyanate by the total number of moles of active hydrogen groups such as hydroxyl groups in a polyol and multiplying the result by 100, and is calculated as [NCO equivalent of isocyanate / active hydrogen equivalent × 100].
[0026] (Water C) Water C is used as a blowing agent. The water C is not particularly limited, and examples thereof include distilled water, ion-exchanged water, ultrafiltered water, and pure water. As a foaming agent, a low-boiling organic solvent (such as an alkyl fluoride compound or an alkyl chloride compound) may be used in combination with water. Also, a gas such as nitrogen gas or air may be mixed into the urethane raw material liquid.
[0027] (Catalyst D) Examples of catalyst D include organometallic compound catalysts and amine catalysts. Examples of organometallic compound catalysts include organometallic catalysts such as tin-, titanium-, bismuth-, and nickel-based catalysts, and examples of such catalysts include organotin compounds such as stannous octoate and dibutyltin dilaurate. As the amine catalyst, tertiary amines are preferable, and examples of the amine catalyst include monoamines, diamines, triamines, cyclic amines, alcohol amines, and ether amines, such as triethylenediamine, triethylamine, n-methylmorpholine, n-ethylformoline, N,N,N',N'-tetramethylbutanediamine, and 1,4-diazabicyclo[2.2.2]octane. The catalyst may be used alone or in combination of two or more kinds.
[0028] (Flame retardant E) As the flame retardant E, a combination of expanded graphite, a phosphorus-based flame retardant, and aluminum hydroxide is used.
[0029] By appropriately adjusting the amount of each flame retardant added, flame retardant E can impart high flame retardancy to the resulting polyurethane foam as well as low 25% compression hardness and low 50% compression set. Examples of expanded graphite include well-known expanded graphite obtained by treating highly crystalline graphite (natural graphite, pyrolytic graphite, kish graphite, etc.) with an acid (sulfuric acid, nitric acid, etc.) and then expanding the spaces between the graphite crystal layers by heating. Phosphorus-based flame retardants are flame retardants that contain phosphorus (P). Examples of phosphorus-based flame retardants include tricresyl phosphate, tri(β-chloroethyl) phosphate, tri(dichloropropyl) phosphate, tri(dibromopropyl) phosphate, and 2,3-dibromopropyl-2,3-chloropropyl phosphate.
[0030] (Other ingredients) Other components include a crosslinking agent.
[0031] Examples of the crosslinking agent include diols. Examples of the diols include aliphatic diols having 3 to 20 carbon atoms, such as 1,4-butanediol, trimethylolpropane, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 3-methyl-1,5-pentanediol (methylpentanediol), 2-ethyl-1,3-hexanediol, 1,2-hexanediol, 1,2-heptanediol, 2,3-heptanediol, 1,2-nonanediol, 1,2-octanediol, 1,2-decanediol, and 1,2-dodecanediol. These may be used alone or in combination of two or more. They may also be adducts of ethylene oxide, propylene oxide, and the like.
[0032] Examples of other components include, in addition to the above-mentioned crosslinking agent, well-known additives such as antioxidants, colorants, ultraviolet absorbers, antibacterial agents, antifungal agents, etc. These components can be added appropriately within the range that does not impair the effects of the present invention.
[0033] (Content of each component in urethane raw material liquid) -Polyether polyol A content- The content of polyether polyol A is preferably from 25 to 40% by mass, and more preferably from 30 to 35% by mass, based on the polyurethane foam.
[0034] - Content of isocyanate B in diphenylmethane diisocyanate-based products - The content of the diphenylmethane diisocyanate-based isocyanate B is preferably from 70 to 90 parts by mass, and more preferably from 75 to 85 parts by mass, relative to 100 parts by mass of the polyether polyol A. The content of the diphenylmethane diisocyanate-based isocyanate B is preferably from 20 to 35% by mass, and more preferably from 25 to 30% by mass, based on the composition (urethane raw material liquid).
[0035] -Water C content- The content of water C is preferably from 0.2 to 0.5 parts by mass, and more preferably from 0.3 to 0.4 parts by mass, relative to 100 parts by mass of polyether polyol A. The content of water C is preferably from 0.07 to 0.17% by mass, and more preferably from 0.1 to 0.14% by mass, relative to the composition (urethane raw material liquid). When the content of water C is within the above range, the apparent density of the resulting polyurethane foam becomes appropriate, and a low 25% compression hardness is easily obtained. In addition, the decrease in flame retardancy due to the decrease in apparent density is easily suppressed.
[0036] -Catalyst D content- The content of catalyst D is preferably from 0.02 to 0.1 parts by mass, and more preferably from 0.04 to 0.08 parts by mass, relative to 100 parts by mass of polyether polyol A. The content of catalyst D is preferably from 0.007 to 0.03 mass %, and more preferably from 0.014 to 0.027 mass %, relative to the composition (urethane raw material liquid).
[0037] -Flame retardant E content- The content of the flame retardant E is preferably from 60 to 165 parts by mass, and more preferably from 70 to 150 parts by mass, based on 100 parts by mass of the polyether polyol A. The content of the flame retardant E, in terms of mass ratio to the composition (urethane raw material liquid), is preferably from 0.23 to 0.45, and more preferably from 0.26 to 0.41. When the content of the flame retardant E is within the above range, it is easy to obtain a desired high flame retardancy, and it is also easy to obtain a low 25% compression hardness and a low 50% compression set.
[0038] <Expanded graphite content> The content of the expandable graphite contained in the flame retardant E is preferably from 30 to 90 parts by mass, and more preferably from 40 to 80 parts by mass, based on 100 parts by mass of the polyether polyol A. The content of the expandable graphite contained in the flame retardant E is, in terms of mass ratio to the composition (urethane raw material liquid), preferably 0.11 to 0.27, and more preferably 0.15 to 0.25. When the content of the expanded graphite contained in the flame retardant E is within the above range, a char layer (thermal insulating carbonized layer) is sufficiently formed, and the desired high flame retardancy is easily obtained. In addition, dripping of combustion products due to excessive expansion of the expanded graphite is suppressed. In addition, low 25% compression hardness and low 50% compression set are easily obtained.
[0039] <Content of phosphorus-based flame retardants> The content of the phosphorus-based flame retardant contained in the flame retardant E is preferably from 5 to 50 parts by mass, and more preferably from 15 to 40 parts by mass, relative to 100 parts by mass of the polyether polyol A. The content of the phosphorus-based flame retardant contained in the flame retardant E is, in terms of mass ratio to the composition (urethane raw material liquid), preferably from 0.02 to 0.16, and more preferably from 0.05 to 0.13. When the content of the phosphorus-based flame retardant contained in the flame retardant E is within the above range, the formation of a char layer (thermal insulating carbonized layer) and the radical trapping effect are sufficient, making it easier to obtain the desired high flame retardancy. In addition, the dripping of combustion products due to the plasticizing effect is less likely to occur. In addition, the plasticizing effect is reduced, making it easier to obtain a low 50% compression set.
[0040] <Aluminum hydroxide content> The content of aluminum hydroxide contained in the flame retardant E is preferably from 5 to 40 parts by mass, and more preferably from 10 to 30 parts by mass, based on 100 parts by mass of the polyether polyol A. The content of aluminum hydroxide contained in the flame retardant E is, in terms of mass ratio to the composition (urethane raw material liquid), preferably from 0.025 to 0.13, and more preferably from 0.03 to 0.10. When the content of aluminum hydroxide contained in the flame retardant E is within the above range, the cooling effect by the endothermic dehydration reaction is sufficient, and the desired high flame retardancy is easily obtained. In addition, the increase in hardness is suppressed, and a low 25% compression hardness is easily obtained.
[0041] (Properties of polyurethane foam) -Thickness- The polyurethane foam according to this embodiment has a thickness of preferably 2 to 6 mm, more preferably 2 to 4 mm, and further preferably 2 to 3 mm.
[0042] The thickness is measured by the following method. The sample to be measured is prepared in an environment of 23±3°C. Next, using a digital gauge, a probe with a diameter of Φ10 mm is used to measure the thickness of the sample with an accuracy of 1 / 100 mm under a load of approximately 0.6 N.
[0043] -Apparent density- The apparent density of the polyurethane foam according to this embodiment is preferably 270 to 370 kg / m 3 and more preferably 290 to 350 kg / m 3 , more preferably 300 to 340 kg / m 3 The apparent density of polyurethane foam is 270 kg / m 3 When the apparent density of the polyurethane foam is 370 kg / m or more, problems in terms of mechanical strength are unlikely to occur. 3 If it is equal to or less than this, a low 25% compression hardness is easily obtained. In particular, the polyurethane foam according to this embodiment has a thickness of less than 6 mm and an apparent density of 270 to 370 kg / m 3 It is preferable that the polyurethane foam is a polyurethane foam having the formula: Apparent density: 270-370kg / m 3 Within this range, it is possible to achieve flame retardancy of V-0 while maintaining a low hardness of 0.1 MPa or less at 25% compression and high recovery with a residual set at 50% compression of 5% or less.
[0044] The apparent density is measured by the following method. First, prepare a sample to be measured (approximate dimensions: length 100 mm x width 100 mm x thickness measurement value) in an environment of 23±3°C. Next, measure the mass weight of the sample with an accuracy of 1 / 100 g using a precision balance. Next, use a digital gauge to measure the thickness dimension of the sample with an accuracy of 1 / 100 mm at nine locations using a probe with a diameter of Φ10 mm and a load of approximately 0.6 N, and calculate the average value. The length and width dimensions of the sample are measured at three locations each using digital calipers, and the average is calculated. The volume of the sample is calculated from the obtained dimensions. The apparent density is then calculated using the formula: apparent density = mass weight / volume.
[0045] -25% compression hardness- The 25% compression hardness of the polyurethane foam according to this embodiment is preferably 0.1 MPa or less, more preferably 0.08 MPa or less, and even more preferably 0.05 MPa or less, from the viewpoint of low hardness. The 25% compression hardness can be measured in accordance with JIS K 6400-2 (2012). Specifically, a sample of 30 x 30 mm is punched out from the object to be measured. If the thickness is 10 mm or less, the sample is laminated to a thickness of 10 mm or more. Then, using Shimadzu Corporation's "Autograph AG-X Precision Universal Testing Machine," the sample is compressed by 25% of its thickness at a compression speed of 10 mm / min, and the 25% compression hardness is measured.
[0046] -50% compression residual strain- The 50% compression set of the polyurethane foam according to this embodiment is preferably 5% or less, more preferably 3% or less, and even more preferably 1% or less, from the viewpoint of restoring property.
[0047] The 50% compression residual strain can be measured in accordance with JIS K6400-4 (2012). Specifically, a sample measuring 30 mm in length and 30 mm in width is punched out from the object to be measured. Next, two smooth compression metal plates that do not easily deform are used to compress the sample parallel to 50% of its thickness, and the sample is kept in an oven at 70°C for 22 hours. The sample is then removed from the compression plates and left at room temperature for 30 minutes before the thickness is measured. The compression residual strain is then calculated using the following formula.
[0048] Compressive residual strain (%) = {(thickness before test - thickness after test) / thickness before test} x 100
[0049] -Flame retardant- The flame retardancy of the polyurethane foam according to this embodiment preferably satisfies the V-0 standard of the UL-94 vertical flame test.
[0050] Flame retardancy can be evaluated according to the UL-94 vertical flame test. Specifically, the upper end of the burner tube is positioned 10±1 mm from the lower end of the test piece, the flame is applied perpendicularly to the centre of the test piece, and this distance is maintained for 10±0.5 seconds to check for combustion of the test piece and ignition of the absorbent cotton by the falling molten material. Flame retardancy is classified into three levels: V-0, V-1, and V-2. The closer to V-0, the more flame retardant the material is. If the burning time is 10 seconds or less, or 30 seconds or less, and there is no molten material falling while burning, the material is classified as V-0 to V-1. If there is molten material falling while burning, the material is classified as V-2.
[0051] (Method of manufacturing polyurethane foam) The method for producing a polyurethane foam according to this embodiment includes the steps of: A step of extruding a composition including polyether polyol A, a diphenylmethane diisocyanate-based isocyanate B, water C, a catalyst D, and a flame retardant E including expandable graphite, a phosphorus-based flame retardant, and aluminum hydroxide from a die to obtain a coating film; Heating the coating; has.
[0052] A specific example of the step of obtaining a coating film is a coating step in which a urethane raw material liquid is continuously applied from a die onto a first continuous web (strip) to form a coating film. A specific example of the step of heating the coating film is a heating step of heating and curing the coating film on the first continuous web to form a foam.
[0053] Here, the process includes a second continuous web supplying step in which, after the coating step and before the heating step, a second continuous web (strip) is supplied to the coating film on the first continuous web (strip) and the coating film is sandwiched between the two continuous webs, and the heating step involves heating and hardening the coating film while it is sandwiched between the two continuous webs to form a foam, which has many advantages. In particular, when a coating of urethane raw material liquid is heated and cured to form a foam while sandwiched between two continuous releasable webs, the foam occurs while sandwiched between the two continuous webs, so there is no scattering of the foaming agent, resulting in a high expansion ratio (low density) and a high quality foam (i.e. sponge) can be obtained with a small amount of water.
[0054] The method for producing a polyurethane foam of this embodiment will now be described with reference to the drawings.
[0055] FIG. 1 is a schematic diagram showing an example of an apparatus configuration for carrying out the method for producing a polyurethane foam according to this embodiment. As shown in FIG. 1, a polyurethane foam manufacturing apparatus 100 includes a first web roll 14 that feeds out a first continuous web 14A, a coating device 12 that coats the first continuous web 14A with a urethane raw material liquid, a large-diameter roller 18 that guides the first continuous web 14A fed out from the first web roll 14 to directly below the coating device 12, a second web roll 16 that feeds out a second continuous web 16A, a guide roller 20 that guides the second continuous web 16A onto a coating film 10 on the first continuous web 14A, second conveyor rollers 28A and 28B that guide the coating film 10 of the urethane raw material liquid sandwiched between the two continuous webs 14A and 16A to a heating device 22 and convey a foam (hereinafter referred to as a "urethane foam sheet") 30 heated and hardened by the heating device 22, and a first recovery roller 24 and a second recovery roller 26 that wind up and recover each of the continuous webs 14A and 16A peeled off from the urethane foam sheet 30.
[0056] -Coating process- First, a urethane raw material liquid prepared by mixing and stirring raw material components is continuously applied onto a first continuous web 14A to form a coating film 10.
[0057] As the first continuous web 14, for example, a resin film or a paper body is preferably used. The resin film is not particularly limited as long as it does not deform when heated during the application and heating steps of the urethane raw material liquid. From the standpoint of resistance to the urethane raw material liquid, heat resistance, etc., films of polyester, polypropylene, polymethylpentene, etc. are preferred. If necessary, the surface of the resin film may be subjected to a corona discharge treatment, a plasma treatment, or the like to improve adhesion to the urethane foam sheet.
[0058] In addition, a resin film may be used in which the surface on which the coating film of the urethane raw material liquid is formed has releasability so that the resin film can be easily peeled off after the urethane foam sheet is produced. The resin film having releasability can be prepared by coating one side of the resin film with a silicone release agent, by directly using a resin film having releasability such as polypropylene resin or polymethylpentene resin, or by laminating a resin film having releasability onto a polyester film or the like. When using a paper body, a paper body in which the surface of glassine paper or wood-free paper is coated with polyethylene or polypropylene, or a paper body further coated with a silicone release agent, etc., is used. The surface of the release film or paper body release paper can also be given a matte finish or a grain pattern to enhance the design and texture.
[0059] As the first continuous web 14A used in the present invention, a resin film having a silicone release agent applied on one side or a resin film having release properties is preferable because the foam solidifies quickly and has high thickness accuracy.
[0060] A die coater is used as the coating device 12 for coating the urethane raw material liquid onto the first continuous web 14A. The urethane raw material liquid is introduced into a die from a discharge nozzle and coated onto the continuous web.
[0061] The thickness of the coating film 10 may be determined depending on the intended use of the foam (polyurethane foam), but is preferably 0.5 to 5 mm from the viewpoints of the foaming ratio and the intended thickness of the urethane foam sheet.
[0062] -Second continuous web supply process- A second continuous web 16A is fed onto the coating film 10 on the first continuous web 14A, and the coating film 10 is sandwiched between the two continuous webs 14A, 16A. The second continuous web 16A can be a resin film or a paper body as exemplified in the description of the first continuous web 14A. From the viewpoint of facilitating peeling of the continuous web from at least one side of the urethane foam sheet 30 after the heating step, it is preferable that at least one of the first continuous web 14A and the second continuous web 16A is a continuous web whose surface in contact with the coating film 10 has releasability.
[0063] The second continuous web 16A is continuously unwound from the second web roll 16 around which the second continuous web 16A is wound, and is placed over the coating film 10 on the first continuous web 14A. As a result, the coating film 10 is sandwiched between the two continuous webs 14A, 16A.
[0064] Although the device shown in FIG. 1 is configured to sandwich the coating film 10 between two continuous webs 14A, 16A, after forming the coating film on the first continuous web 14A, the process may proceed to the next heating step without covering it with the second continuous web 16A.
[0065] -Heating process- The coating film 10 is sandwiched between two continuous webs 14A, 16A and conveyed into a heating device 22 where it is cured by heating. The heating temperature for curing is preferably 80 to 120° C., and curing is preferably achieved within this temperature range for 5 to 20 minutes. The heating device 22 may be an infrared heater, an electric heater, a gas combustion furnace, or the like.
[0066] - Peeling process - The urethane foam sheet 30 foamed and cured by the heating step is transported by the second transport roller 28A and the first transport roller 28B, and the continuous webs 14A, 16A may be wound up while being in close contact with the urethane foam sheet 30, or, if the continuous webs 14A, 16A are release webs, as shown in Fig. 1, the release web is peeled off from the urethane foam sheet 30 while the urethane foam sheet 30 is transported by the second transport roller 28A and the first transport roller 28B and is wound up and recovered by each of the recovery rollers 24, 26. The first recovery roll 24 and the second recovery roll 26 which have recovered the continuous webs 14A, 16A can be reused as the first web roll 14 and the second web roll 16, which are supply rolls.
[0067] Through the above steps, a polyurethane foam consisting of a urethane foam sheet (foam) can be continuously produced.
[0068] (Polyurethane foam) The polyurethane foam according to this embodiment can be suitably used for applications such as cushioning materials for automobile batteries, which require high flame retardancy. EXAMPLES
[0069] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following, "parts" are by weight unless otherwise specified.
[0070] <Examples 1 to 24 and Comparative Examples 1 to 9> The components shown in Tables 1 and 2, excluding isocyanate, were mixed with stirring to obtain a polyol-based solution, and the solution was heated to 50°C. Next, isocyanate was mixed with the obtained polyol solution by stirring according to Tables 1 and 2 to obtain a urethane mixed solution. Next, the obtained urethane mixture was uniformly applied onto a PET film (thickness 100 μm) whose surface had been treated with a release agent, and then another PET film (thickness 100 μm) whose surface had also been treated with a release agent was placed on top, and the urethane mixture was sandwiched between the two PET films. In this state, the plate was heated in an oven at 80° C. for 5 minutes, and immediately thereafter further heated in an oven at 120° C. for 10 minutes. After the heating was completed, the product was taken out of the oven, the PET film was removed, and a polyurethane foam having an autogenous skin on the surface and a thickness shown in Tables 1 and 2 was prepared.
[0071] A polyurethane foam was produced in the same manner as in Example 1, except that the composition in Tables 1 and 2 was used.
[0072] <Physical property measurements> The following physical properties of the polyurethane foam obtained in each example were measured according to the methods described above. Thickness (mm) Apparent density (kg / m 3 ) 25% compression hardness (MPa) 50% compression residual strain (%) (measurement conditions: 70℃, 22 hours)
[0073] <Flame retardancy> Test pieces for flame retardancy tests (length 125±5 mm×width 13±0.5 mm, thickness is the thickness of the urethane foam of each example) were taken from the urethane foam of each example. The upper end of the burner cylinder was positioned 10±1 mm from the lower end of the test piece, and the flame was applied vertically to the center of the test piece. This distance was maintained for 10±0.5 seconds. The test piece was checked for combustion and for the ignition of the absorbent cotton by the molten falling material, and evaluated according to the following criteria. Flame Retardancy Evaluation Criteria ◯: Five out of five test pieces burned for 10 seconds or less, no burning until clamped, no cotton ignition △: 3 to 4 out of 5 test pieces burned for less than 10 seconds, no burning until clamped, no cotton ignition ×: Burning time of 10 seconds or less for 2 or less of 5 test pieces, no burning until clamped, no cotton ignition
[0074] Details of the materials used in the examples and comparative examples are given below. -Polyether polyol- Product name: Sannix FA-703V, Manufacturer: Sanyo Chemical Industries
[0075] -Expanded graphite- Product name: SFF-32, Manufacturer: Chuetsu Graphite Industry Co., Ltd. -Liquid phosphorus-based flame retardant- Aliphatic condensed phosphate ester, product name: DAIGUARD-880 Manufacturer: Daihachi Chemical Industry -Aluminum hydroxide- ·Product name: CW-375HT, Manufacturer: Sumitomo Chemical
[0076] -Crosslinking agent- 1,4-Butanediol, Manufacturer: BASF Idemitsu Polyether polyol, Product name: Actocol IR-94, Manufacturer: Mitsui Chemicals SKC Polyurethane However, the crosslinking agent used in Example 1-2 was 6.5 parts by mass of 1,4-butanediol and 6.5 parts by mass of polyether polyol, totaling 13 parts by mass. In addition, in Examples 3 to 24 and Comparative Examples 1 to 9, 7.5 parts by mass of 1,4-butanediol and 7.5 parts by mass of polyether polyol were used as the crosslinking agent, totaling 15 parts by mass.
[0077] -catalyst- Aliphatic tertiary amine composition, product name: DABCO 33LV, manufacturer: Evonik Japan Dibutyltin dilaurate, product name: Neostan U-100, manufacturer: Nitto Kasei However, the catalyst used in Examples 1 to 24 and Comparative Examples 1 to 9 was 0.03 part by mass of an aliphatic tertiary amine composition and 0.03 part by mass of dibutyltin dilaurate, totaling 0.06 part by mass.
[0078] -Diphenylmethane diisocyanate-based isocyanate B- Polyisocyanate modified product, Product name: DC-6974, Manufacturer: Tosoh
[0079] [Table 1-1]
[0080] [Table 1-2]
[0081] [Table 2]
[0082] From the results in Tables 1 and 2 above, it is apparent that this example is excellent in flame retardancy, low hardness, and recovery. Furthermore, Examples 6, 7, 10, 11, 14, 15, 18, 19, 22, and 23 achieved flame retardancy of V-0. [Explanation of symbols]
[0083] 10 Coating 12 Coating equipment 14 First Web Roll 14A First Continuous Web 16 2nd Web Roll 16A Second Continuous Web 18 Large diameter roller 20 Guide roller 22 Heating device 24 First recovery roll 26 Second recovery roll 28A Second conveyor roller 28B First conveyor roller 30 Foam (urethane foam sheet) 100 Polyurethane foam manufacturing equipment
Claims
1. Polyether polyol A; Isocyanate B of the diphenylmethane diisocyanate series; Water C, Catalyst D; and a flame retardant E containing expanded graphite, a phosphorus-based flame retardant, and aluminum hydroxide; A polyurethane foam comprising a foam of a composition comprising:
2. The content of the expanded graphite is 40 to 80 parts by mass relative to 100 parts by mass of the polyether polyol A, The content of the phosphorus-based flame retardant is 15 to 40 parts by mass relative to 100 parts by mass of the polyether polyol A, The polyurethane foam according to claim 1, wherein the content of the aluminum hydroxide is 10 to 30 parts by mass per 100 parts by mass of the polyether polyol A.
3. The thickness is less than 6 mm and the apparent density is 270 to 370 kg / m 3 2. The polyurethane foam according to claim 1,
4. 2. The polyurethane foam according to claim 1, having a 25% compression hardness of 0.1 MPa or less.
5. 2. The polyurethane foam according to claim 1, having a 50% compression set of 5% or less.
6. A step of extruding a composition containing polyether polyol A, a diphenylmethane diisocyanate-based isocyanate B, water C, a catalyst D, and a flame retardant E containing expandable graphite, a phosphorus-based flame retardant, and aluminum hydroxide from a die to obtain a coating film; Heating the coating; The method for producing a polyurethane foam comprising the steps of:
7. The content of the expanded graphite is 0.15 to 0.25 in terms of mass ratio relative to the composition, The content of the phosphorus-based flame retardant is 0.05 to 0.13 in terms of mass ratio relative to the composition, The method for producing a polyurethane foam according to claim 6, wherein the content of the aluminum hydroxide is 0.03 to 0.10 in terms of a mass ratio relative to the composition.
Citation Information
Patent Citations
Light elastic fire retardance die block and preparation method thereof
CN105860023A
Polyurethane foam laminate and method for manufacturing the same, and gasket
JP2010247532A
Highly flame-retardant polyurethane foam
JP2011252111A
Method for producing foam urethane sheet
JP2013256558A
Sheet and production method for sheet
JP2022139694A